ACEPROMAZINE ASSOCIATED WITH PUDENDUM AND HEMORROIDAL NERVE ANESTHESIA IN BOVINE AND BUFFALO PENIS EXPOSURE (Veterinária Notícias, 2014)
ACEPROMAZINE ASSOCIATED WITH PUDENDUM AND HEMORROIDAL NERVE ANESTHESIA IN BOVINE AND BUFFALO PENIS EXPOSURE